Effects of Zr substitution on structure and thermoelectric properties of Bi2O2Se - Zhuang Fu; Jia-Ling Jiang; Song-Tao Dong; Miao-Cheng Yu; Lijun Zhao; Lei Wang; Shu-Hua Yao (Journal of Materials Research and Technology, 2022)
In this study, the facile synthesis method of Bi2−xZrxO2Se (x = 0, 0.02, 0.04, and 0.06) ceramics using a combining the high-energy ball milling and cold pressing was reported. The effects of zirconium (Zr) doping on the microstructure and thermoelectric properties of Bi2O2Se were systematically investigated. The results indicate that the powder samples were synthesized as a single phase with no impurities. With increasing Zr content, conductivity increased from 13.49 S to 34.91 S cm−1 at 773 K. The thermal conductivity of Bi1.98Zr0.02O2Se was also reduced to 0.51 W m−1 K−1. The maximum power factor (PF) value of the Bi1.96Zr0.04O2Se sample was 186 μW m−1 K−2 at 773 K. A peak ZT of around 0.27 was achieved for the Bi1.96Zr0.04O2Se sample, which is approximately 2.4 times greater than that of un-doped one (∼0.11). The results indicate that Zr-doping significantly improves the thermoelectric properties of the Bi2O2Se system.